Efficacy of combined colorectal cancer treatment in senile patients - Tsarkov, P.V.; Markaryan, D.R.; Nekoval, V.M. (Rossiĭskiĭ zhurnal gastroėnterologii, gepatologii, koloproktologii, 2018)
Aim of investigation.To estimate efficacy of combined treatment of colorectal cancer (CRC) in senile patients, to determine risk factors for postsurgical complications and evaluate postoperative mortality. Material and methods. The retrospective and prospective analysis of primary CRC patients, who were operated in The First Sechenov Moscow State Medical University and Petrovsky National Research Center of Surgery in April, 2006 to May, 2014 was carried out. Overall 122 patients with CRC of the II-IV stage of senile age were selected, whose mean age was 79 (75-95) years. Preoperative comorbidity assessment and perioperative complications risk were assessed by Charlson comorbidity index and ASA physical status classification system. Cr-POSSUM scoring system was applied to predict postoperative (30-day) mortality. Overall and cancer-specific survival rate were assessed taking into account comorbidity of patients and prescribed adjuvant therapy. Results. The average Charlson score taking into account age of the patient was 7.6±2.4. Forty seven patients (39%) were classified as ASA≥3. The predicted postoperative motility (Cr-POSSUM) was 13.2%. In 106 (87%) patients colon or rectum resection with formation of primary interintestinal anastomosis and D3 lymph node dissection, at 11 (9%) - abdominal and perineal rectum extirpation is executed, 5 patients had obstructive Hartmann operation. Patients with the IV stage of CRC underwent standard volume surgery with high-grade lymph node dissection due to the high risk of obstruction or tumor bleeding. Achieved 30-day postoperative mortality was 4.9%, overall 5-year survival rate - 67.3±5.6%, cancer-specific survival - 70.1±4.4%. In group of patients with III and IV stages of CRC who received postoperative adjuvant therapy, the tendency to higher total survival was noted, however only cancer-specific survival scores had statistically significant differences in this subgroup. Conclusions. Multidisciplinary approach to CRC treatment provides achievement of satisfactory postoperative mortality in senile patients (4.9% versus predicted 13.2%) along with satisfactory total and cancer-specific 5-year survival rate. Postoperative adjuvant therapy significantly improves treatment results for third stage CRC, however the objective indications for adjuvant therapy are yet to be established. Due to complex drugto-drug interactions specificity of metabolism and biological tumor properties, cross-reactions of concomitant diseases in senile patients each step of combined treatment should be discussed at multidisciplinary consultation.